Digitalization and Cyber Security Policies in Uzbekıstan's Institutions and Sectors in One Belt One Road Project - Mithat Baştuğ; Muhammed Ali Yetgin (İmgelem)
The diffusion of information and communication technologies (ICT) into a rapidly growing area of global trade has contributed significantly to the gains made by companies and governments. Increasing consumption at the international level and the desire for faster and more reliable delivery of goods have led to the emergence of new sectors. In this context, states, other government agencies, and the private sector have sought to enhance their bilateral relations and investments and establish strategic partnerships to develop new fast, and reliable trade networks. While actions and activities in cyberspace and digital spaces have provided significant convenience and opportunities, they have also led to significant security concerns. The purpose of this study is to examine and evaluate the contribution of the One Belt, One Road (OBOR) initiative to the digitalization of Uzbekistan and the policies pursued by Uzbekistan in this regard, and to investigate the effects of public and private sector institutional cooperation in the One Belt, One Road project. The content analysis method was applied, one of the qualitative research methods. The study was also strengthened with the SWOT analysis method. By comparing relevant documents and sources on the subject, the aim of the study was concluded. The studies carried out to increase Uzbekistan's cyber capacity, the importance of maintaining strong cyber security policies through technology transfer, the challenges and legal regulations, institutional and sectoral cooperation, and their effects are the problem statements within the outline of the purpose of the study.